Pengaruh Return On Asset Terhadap Return Saham Dengan Struktur Modal Sebagai Variabel Intervening (Studi Kasus Pada Perusahaan Telekomunikasi Yang Tercatat Di BEI Periode Tahun 2009-2016) - Eka Wahyuni (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aims to describe 1) the effect of return on asset variables on stock returns, 2) the effect of return on assets on capital structure, 3) the effect of capital structure on stock returns. Variable in this research is return on asset, stock return, capital structure. The sample of this research are 5 telecommunication companies listed in Indonesia Stock Exchange year 2009-2016. The data in this research are secondary data obtained from Indonesian Stock Exchange while the data analysis technique uses simple linear regression analysis, classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test, and coefficient of determination test (R2). The results showed that there is a positive influence and significant return on assets on stock returns on telecommunication companies of 0.000 (p <0.05). There is a positive influence and significant return on asset to capital structure in telecommunication company is 0,004 (p <0,05). There is a positive and significant effect of capital structure on stock return on telecommunication company by 0,140 (p <0,05). So there is influence between return on asset to stock return with capital structure as intervening variable at Indonesian telecommunication company.